Electronically Tunable Differential Difference Current Conveyor Using OTAs - Chuthitep Sukhawit; Bancha Burapattanasiri; Usa Torteanchai; Somkiat Lerkvaranyu; Boonying Knobnob; Montree Kumngern (My University, 2021)
This paper presents a new electronically tunable differential difference current conveyor (DDCC) using operational transconductance amplifiers (OTAs). Unlike conventional DDCC, the proposed DDCC offers current gain between z- and x-terminal that can be controlled electronically by bias currents. The DDCC-based OTA can be investigated both simulation and experiment tests. The proposed DDCC is used to implement a quadrature oscillator to confirm workability.
Keywords: Analog and Mixed-Signal Circuit Design; Neuroscience and Neural Engineering; Advanced Memory and Neural Computing